EXTRACTING SOLUTIONS FOR QUANTIFICATION OF ZINC, COPPER AND MANGANESE IN A SANDY SOIL - ORTIZ, Fábio Rogério; BRITO, Osmar Rodrigues; BORKERT, Clóvis Manuel (Scientia Agraria, 2007)
The objective of this research work was to evaluate and to compare the efficiency of two soil extracting solutions, Mehlich-1 and DTPA (Diethylenetriaminepentaacetic acid) for analysis of the micronutrients Zn, Cu, and Mn. Soil samples were taken from the plowing layer (0-20 cm deep) of an Haplorthox sandy soil (Latossolo Vermelho escuro) in Mamborê County, State of Paraná, Brazil. After air-drying, the samples were than crushed and passed through a 2 mm stainless steel screen for later physical and chemical analyses. In the soil extracts, the micronutrients were determined by an atomic absorption spectrophotometer. The experimental design was a complete randomized design with two treatments and 20 replications. The coefficients of correlation between the extracts Mehlich-1 and DTPA (0.93; 0.88; 0.75 for zinc, manganese and copper respectively) were significant, thus indicating that both extractors can be used in the quantification of these nutrients. The Mehlich-1 solution, however, substitutes the DTPA with advantages because it is more adapted to laboratory routine.